Impact of Entrepreneurship Education and Policy on Vietnamese Youth’s Entrepreneurship Readiness and Intentions - Ho, Anh Thi Dieu; Hoang, Van Thi Thuy; Tran, Na Le Thi; Nguyen, Sao Nu Hai; Hoang, Thuong Thi Cam; Nguyen, Thuy Minh Vu (International Review of Management and Marketing, 2024)
This study aims at investigating impact of entrepreneurship education and policy on Vietnamese youth’s entrepreneurship readiness and intentions. The structural equation modeling (SEM) was applied to explore the relationship among different factors. In this research, the moderating variable was entrepreneurship mentor while intermediate variables were comprised of age, gender as well as educational background. The primary data was collected through online survey questionnaire with Vietnamese youngsters. There were 583 valid responses, which were processed with SPSS and AMOS software. The analyzed data demonstrated that 5 hypotheses were accepted. This proved that entrepreneurship intention was influenced by entrepreneurship policy and education. The factor of entrepreneurship mentor played the intermediate role within the relationship between entrepreneurship readiness and intention of Vietnamese youth.